Introduction to The Earth Field In Bukit Batu Putih, Samarinda City, East Kalimantan - Sidik, Hamzah; SN, Rio Syaputra; Vannes, Vannes; Fernandez, Jimmy; Yusnul, Yusnul; Kusuma, Wira (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This Introduction to Earth Science Field Lecture activity was conducted at Bukit Batu Putih, Samarinda City, which is the Balang Island Formation (Tmpb). This location was chosen because of the dominance of limestone in the area and the significant limestone mining activities. This study aims to understand the local geological characteristics, identify limestone types, and analyze the impact of mining on the surrounding environment. The methodology used in this study includes field observation, geological mapping, and visual analysis and limestone sample assessment. Field observations were conducted to identify the structure and texture of limestone and geological formations around the location. Geological mapping was conducted to map the distribution of limestone and understand the stratigraphic relationship between rock layers. The results of the study indicate that limestone consists of clastic and fossiliferous limestone types, which are formed from calcium carbonate deposits. Mining activities in this area have revealed many limestone layers that have economic potential. However, mining also has environmental impacts, such as changes in land morphology and degradation of water quality. The conclusion of this study emphasizes the importance of understanding regional geology and limestone characteristics for better resource management. Recommendations are provided for improving environmentally friendly mining practices and conservation efforts to maintain the balance of the ecosystem in Bukit Batu Putih.